Kualitas Fisik, Mikrobiologis, dan Organoleptik Daging Ayam Broiler pada Pasar Tradisional di Bogor - Hajrawati, Hajrawati; M., Fadliah; Wahyuni, Wahyuni; Arief, I. I. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
In Indonesia, broiler meat is available abundant mainly in traditional market. Unfortunately, this kind of meat is perishable most physical, organoleptic, and microbiological deterioration. To conserve consumers from low quality of meat, this study was conducted to evaluate the physical, organoleptic, and microbiological quality of meat. Meat evaluated was obtained from three traditional markets determined purposively, namely A market, B market, and C market. The physical quality measured were pH and aw; the microbiological quality were total plate count and E. coli number; the organoleptic were meat color, texture, aroma that value in hedonic and hedonic rank test. This study showed that physically the meat was not really decrease although it had pH higher than normal pH of meat. The value of aw reached was 0.84-0.85. The microbial contaminant was higher than the number of microbial allowed. However, organoleptic value indicated that meat were acceptable for panelists.